Enhancing embryogenesis efficiency in sweet pepper (Capsicum annuum var.grossum) via anther culture optimization - JHA, KAUSHIK; CHOUDHARY, PRADEEP KUMAR; AGARWAL, ARUN (The Indian Journal of Agricultural Sciences, 2025)
Sweet pepper [Capsicum annuum var. grossum (L.)], valued for its nutritional benefits like high vitamin C and carotenoid levels, requires efficient breeding methods to meet demand. Double haploid (DH) technology provides a rapid alternative to traditional methods by generating homozygous lines in a single generation. The present study was carried out during 2021 and 2022 at ACSEN Agriscience Pvt. Ltd. Kullu, Himachal Pradesh to determine the ideal conditions for inducing embryo formation from anthers in 4 sweet pepper hybrids, viz. Asha, Sympathy, Nemalite, and Indra. The study investigated the impact of various factors on embryo development in sweet pepper anther cultures, including cold pre-treatment of buds, heat shock, different concentrations of sucrose and activated charcoal, and the application of plant hormones 2,4-D, and kinetin. Results indicated that a 24 h cold pre-treatment at 4°C accompanied by a 10-days heat shock at 35°C significantly enhanced embryogenic responses, particularly in genotype Asha, which showed a peak response of 39.3 embryos. The optimal sucrose (4%) and activated charcoal (0.50 gm/litre) concentrations further improved embryogenesis, with Asha achieving up to 48.7 embryos. The balance of 2, 4-D (0.50 mg/litre) and kinetin (4.0 mg/litre) was also crucial. Genotype Asha showed the highest response of 43.0 embryos under these specific conditions. Genotype-specific responses highlighted the importance of genetic variability in androgenesis studies, with Asha giving the best result, achieving the highest average of 34.7 embryos with a 23.1% embryogenic response in the combined experiment using the most effective treatment combinations. This study highlights how optimized anther culture enhances embryo formation, aiding the development of new sweet pepper cultivars and improving breeding efficiency with DH technology.